2013
DOI: 10.1001/jamadermatol.2013.6812
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surgical and Minimally Invasive Facial Cosmetic Procedures on Psychosocial Outcomes

Abstract: The current literature suggests that a number of psychosocial domains may improve following facial cosmetic surgery, although the quality of this evidence is limited (grade of recommendation 2A). Despite the dramatic rise in nonsurgical cosmetic procedures, there is a paucity of information regarding the impact of chemodenervation and soft-tissue augmentation on psychosocial functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 47 publications
2
42
0
2
Order By: Relevance
“…These results are consistent with the idea that the primary expectation in patients seeking minimally invasive facial procedures is to look as natural as possible to reflect the personality and expression, and to protect inner contentment or self-esteem. 29 The current literature suggests that a number of psychosocial domains may be improved following facial cosmetic procedures 30 and a high satisfaction probably mediates more well-being and self-esteem. Fullfacial treatment may reduce negative mood and affect QoL.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the idea that the primary expectation in patients seeking minimally invasive facial procedures is to look as natural as possible to reflect the personality and expression, and to protect inner contentment or self-esteem. 29 The current literature suggests that a number of psychosocial domains may be improved following facial cosmetic procedures 30 and a high satisfaction probably mediates more well-being and self-esteem. Fullfacial treatment may reduce negative mood and affect QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies showed moderate improvements in psychosocial functioning, including a self-body image, self-esteem, and life quality. Unluckily, the global quality of evidence is limited due to a lack of control groups, short follow-up periods, or loss to follow-up (10). The current evidence shows that a number of psychosocial realms can improve following facial cosmetic procedures.…”
Section: Dear Editormentioning
confidence: 99%
“…Millions of cosmetic and surgical procedures of the face are administrated each year; however, objective clinical criteria that assess surgical procedures, such as complication rates, have limited efficiency when applied to cosmetic procedures. While there might be subjective improvements in cutaneous body image, it is very important to assess if these procedures have an effect on patients in other domains, such as psychosocial functioning (10).…”
Section: Dear Editormentioning
confidence: 99%
“…Studies evaluating psychological outcomes of orthognathic surgery, which involves manipulation of the facial skeleton to restore anatomic and functional relationships in patients with dentofacial abnormalities, have shown the desire for improved appearance to be a major consideration for patients seeking such surgery [4]. Several studies report that patients receiving corrective facial surgery display improvements in measures of personality adjustment, such as psychosis or neurosis, as well as improvements in selfconcept, self-identity, self-esteem, and self-conflict [4][5][6][7][8][9][10].…”
Section: Corrective Facial Surgery and Self-conceptmentioning
confidence: 99%
“…The relationship between selfconcept, body-image, and appearance is well documented [2,3], and thus facial disfigurement can have profound psychosocial implications. Substantial research has described the benefits of traditional facial reconstruction with respect to self-concept [4][5][6][7][8][9][10]; however, these procedures are often inadequate for more severe facial defects.…”
Section: Introductionmentioning
confidence: 99%